Multisystem involvement of alveolar echinococcosis in a child - Mecit Kantarci; Ummugulsum Bayraktutan; Berhan Pirimoglu; Hayri Ogul; Akgun Oral; Suat Eren; Betul Gundogdu (Journal of Infection in Developing Countries)
Alveolar echinococcosis (AE) is a chronic progressive infestation inducing a slowly progressing, life-threatening tumor-like growth in the liver. It may spread to other organs by regional extension or hematogenous or lymphatic metastasis. Herein, we report a fifteen-year-old patient diagnosed with AE of the liver and simultaneous lung and brain metastasis with a literature review.